PERAN KEPERCAYAAN KUALITAS INFORMASI DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE - Yulia, Yosephine Angelina (Gapenas Publisher, 2024)
Nowadays, online shopping has become a habit for some people, because of the convenience provided, many people think that online shopping is one of the means to find the necessary items such as daily necessities. Besides trust and information quality, risk perception also determines a person in making transactions at Shopee. A higher perception of risk causes higher fear when transacting online, and vice versa. The purpose of this research is to determine the role of trust, information quality and risk perception on purchasing decisions at shopee for the Greater Solo community. The sample of this study was 100 respondents determined by purposive sampling technique. This research instrument is in the form of a questionnaire. The data analysis technique used is PLS-SEM. The t test results show that the variables of trust, information quality and risk perception have a positive and significant effect on purchasing decisions. The ability of the trust, information quality and risk perception variables to explain the purchase decision variable is 41% (Adjusted R Square) and the remaining 59% is influenced by other factors outside the variables studied